Detection of core-skin disbonds in honeycomb composite sandwich structures using highly nonlinear solitary waves. (15th January 2021) - Yoon, Sangyoung; Schiffer, Andreas; Cantwell, Wesley J.; Kim, Tae-Yeon
Abstract: We study experimentally the feasibility of using a solitary wave-based diagnostic scheme for the detection of core-skin disbonds in composite sandwich structures comprising of carbon-fiber/epoxy skins and a Nomex™ honeycomb core. Non-destructive tests are conducted using a vertically aligned granular chain of steel beads placed in direct contact with the skin of the sandwich panel containing core-skin disbonds of various sizes. The incident and reflected nonlinear pulses are recorded at a single location in the chain via an embedded piezoelectric sensor, and the effects of disbond size and skin thickness on the delay and amplitude of the reflected solitary waves are studied. The results show that the existence of a core-skin disbond significantly increases the delay in the formation of reflected solitary waves as compared to the measurements obtained for a pristine panel, and this difference increases with decreasing skin thickness. The proposed method is capable of detecting defects of 4.9 cm 2 area or larger in a sandwich panel with skins as thick as 1.2 mm, while disbonds of 1.8 or 3.1 cm 2 area can only be clearly identified for skin thicknesses up to 0.8 mm. The obtained results demonstrate that the solitary wave-based diagnostic scheme is effective in detecting core-skin disbonds in honeycomb composite sandwich panels, offering a reliable and cost-effective alternative to existing non-destructive test methods.